ANALISIS RASIO BIAYA SUMBERDAYA DOMESTIK USAHA BUDIDAYA RUMPUT LAUT DI INDONESIA - Mira Clenia (Jurnal Bisnis dan Ekonomi, 2008)
The objective of this research was focussed to analyse the domestic resouce cost ratio(DRC) of is effort seaweed from various research location, like Karimun Java, Probolinggo,Sumenep, Klungkung, Badung, Lombok East Island, Sumbawa, Bima, Jeneponto, Palopo, andBulukumba. Result of analysis of domestic resouces cost ratio indicate that the effort seaweed invarious research location can be growth, althought goverment does not support or intervensi.Bulukumba (0,03) represent the area owning lowest the domestic resouce cost ratio, followed byKarimun Jawa (0,03), Probolinggo (0,04), Klungkung (0,07), Sumbawa (0,08), Bima (0,09),Sumenep (0,1), Badung (0,13), Jeneponto (0,3), dan Lombok Timur (0,35).If DRC value < 1means that comodity can be growth, althought goverment does not support or intervensi. In theeffort improving economic growth rate, commodity with value of DRC smaller will get higherpriority in development.Key Words: Domestic Resource Cost Ratio and Seaweed